Melanin thin-films: a perspective on optical and electrical properties. Issue 26 (21st June 2021) - Paulin, J. V.; Coleone, A. P.; Batagin-Neto, A.; Burwell, G.; Meredith, P.; Graeff, C. F. O.; Mostert, A. B.
Abstract : Optical and electrical properties of soluble melanin were discussed based on different chemical structures. Abstract : Melanins are an essential natural pigment found throughout nature. Due to their inherent biocompatibility, optical and electronic properties, the melanins are attracting attention as model materials for sustainable organic optoelectronic and bioelectronic applications. Standard melanin is notoriously insoluble, which complicates processability considerably. Hence, the creation of synthetic derivatives that have similar optical–electronic properties but with increased solubility are avenues of active investigation. In this work, we investigate soluble non-functionalised (NF) and sulfonated (S) melanin derivatives. So far, these new synthetic derivatives' optical and electrical properties have not been explored in full, which would allow their effective application in optoelectronic devices. Our optical results suggest that these materials have high refractive indices and also high dispersion and chromatic aberration. In addition, no significant differences in NF-melanin's charge transport deposited from pure water or aqueous ammonia solution were observed, and S-melanin's functional groups did not affect the hydration-dependence conductivity, only its sensitivity to environmental humidity. The similarities and differences in spectra and values comparing NF and S-melanin are discussed based on their structural differences.